Socioeconomic position in childhood and depressive symptoms in later adulthood in the Czech Republic - Cermakova, Pavla; Pikhart, Hynek; Ruiz, Milagros; Kubinova, Ruzena; Bobak, Martin (Journal of affective disorders, 2020)
BACKGROUND: Depression risk may partly originate from socioeconomic hardship in childhood. We investigated the association of childhood socioeconomic position with depressive symptoms in later adulthood in a Central and Eastern European country. METHODS: We analyzed data from the Czech arm of the Health, Alcohol and Psychosocial factors In Eastern Europe (HAPIEE) study. We estimated the associations of three indicators of childhood socioeconomic position (access to household amenities at age of 10 years, father´s education and mother´s education) with high depressive symptoms, operationalized as ≥16 points on the Center for Epidemiological Studies - Depression 20 scale, controlling for age and sex, current socioeconomic position and other social and health-related factors. RESULTS: The analytical sample included 4,213 individuals (mean age 58 years, 54% women). All three indicators of childhood socioeconomic position were inversely associated with depressive symptoms in age-sex adjusted models (p for trends: access to household amenities p<0.001; mother´s education p<0.001; father´s education p=0.03). Adjustment for current socioeconomic position attenuated the associations of depressive symptoms with access to household amenities (p for trend 0.04) and mother´s education (p for trend 0.05) and virtually eliminated the association with father´s education (p for trend 0.82). LIMITATIONS: Individuals with higher depressive symptoms and more adverse socioeconomic position are likely to be underrepresented in the study sample. Data on childhood socioeconomic position may be reported inaccurately. CONCLUSIONS: Socioeconomic hardship in childhood may have long-lasting consequences on mental health in later adulthood.
Keywords: Depressive symptoms; Humans; Childhood socioeconomic hardship; lidé středního věku; dítě; socioekonomické faktory; Child; duševní zdraví; Female; rizikové faktory; dospělí; lidé; Epidemiology; Europe; Socioeconomic Factors; Adult; společenská třída; ženské pohlaví; Male; Middle Aged; Czech Republic; Lifecourse; stupeň vzdělání; Depression; Social Class; Česká republika; mužské pohlaví; deprese; Educational Status; Evropa; Mental Health; Risk Factors